Assessing MODIS16A2 actual evapotranspiration across three spatial resolutions in Uruguay - Rafael Navas; Guadalupe Tiscornia; Andrés G. Berger; Álvaro Otero (Agrociencia Uruguay, 2021)
Evapotranspiration (ET) is a key process in hydrological systems and, consequently, in agroecosystems. It can be measured or derived with a large variety of models at scales ranging from leaf to catchment. MODIS16A2 is a satellite ET product with 500 meters / 8-day spatio-temporal resolution worldwide. It is based on the Penman-Monteith equation and considers the effect of vegetation dynamics, albedo and land cover. This technical paper compares the ET estimated from MODIS16A2 against the ET estimated at different scales from three reference methods: (1) the INIA-GRAS Water Balance on a country-scale, (2) the SWAT model of the Santa Lucia basin on the catchment scale, and (3) the Eddy Covariance Flux located in Colonia on a farmer scale. The analysis shows similarities between MODIS16A2 and the reference methods depending on seasonality, geographic location and scale of ET estimation. The assumptions about vegetation cover, vegetation dynamics, meteorological forcing and soil characteristics of the reference methods compared with MODIS16A2 ones could explain some deviations in the ET estimations. The results of this work contribute with a first approximation towards the quantification of the uncertainty of MODIS16A2 in Uruguay.